HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PERSONAL HYGIENE PANGAN INDUSTRI RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS KONI KOTA JAMBI TAHUN 2024 - Misroni Herawati Harahap; Novi Berliana; Eko Mirsiyanto (Bajang Institute, 2025)
Good personal hygiene is an important factor in maintaining food safety and public health. In the home industry sector, especially in food processing, the implementation of proper hygiene practices is crucial to prevent contamination and the spread of disease. The study aimed to determine the relationship between knowledge and attitudes with personal hygiene of household industry food in the working area of Koni Health Center, Jambi City. The study used a cross sectional design. The research was conducted in the Koni Health Center working area on August 2-15, 2024. The research sample was 35 household industry workers in the Koni Health Center working area. The research instruments were questionnaires and observation sheets. Data were analyzed using the chi square test. The results showed 65.7% of respondents had poor personal hygiene behavior, 62.9% of respondents had poor knowledge, 54.3% of respondents had poor attitudes, and 62.9% of respondents had poor infrastructure. Bivariate results showed there was a relationship between knowledge (P=0.025) and attitude (p=0.031) with personal hygiene of household industry food in the Koni Health Center working area of Jambi City. there is no relationship between infrastructure and personal hygiene of household industry food in the Koni Health Center working area of Jambi City (p=0.132). Factors associated with personal hygiene of household industrial food in the Koni Health Center working area are knowledge and attitude.